I feel more like myself when I wear my velskoene: Exploring South African male millennial consumers’ attachment to their velskoene - Lombard, Emmy; Taljaard-Swart, Hanri; Jacobs, Bertha (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Due to fast fashion, the lifespan of products like footwear has shortened, with consumers discarding shoes prematurely due to poor quality or for newer options. Extending the product lifespan through product attachment offers a potential solution. While product attachment studies have explored multiple product categories, few have focused on one product within a particular context. This study focuses specifically on the velskoen, a leather footwear style known for being durable and long-lasting. The velskoen has not been formally researched in South Africa, nor has its product attachment been explored. Therefore, the study aims to explore product attachment among millennial males in South Africa, specifically velskoen attachment. Qualitative, semi-structured interviews were conducted with ten participants and focused on four determinants of attachment: memories, pleasure, self-expression, and group affiliation. Object elicitation enabled participants to showcase their velskoene and comfortably chat about them to extract valuable insights. Participants described their memories, how their velskoene allowed self-expression, to which groups they affiliated themselves and their velskoene, the different types of pleasure their velskoene afforded, and product care practices. While memories featured strongly, physical pleasure emerged the most. More often than not, these two determinants complemented each other. Additionally, results showed that the velskoen allowed participants to express themselves and feel connected to specific groups on a cultural and national level. This suggests a notable attachment to velskoene among the male millennials in South Africa, which is linked primarily to pleasure and memories, which causes extended ownership, increased care, and improved sustainability.